How to facilitate psychosocial adjustment in women tested for hereditary breast or ovarian cancer susceptibility? Insights from network analysis. Issue 3 (11th December 2019) - Brédart, Anne; Dick, Julia; Cano, Alejandra; Robieux, Léonore; De Pauw, Antoine; Schmutzler, Rita; Stoppa‐Lyonnet, Dominique; Dolbeault, Sylvie; Kop, Jean‐Luc
Abstract: Background: Increasingly complex genetics counseling requires guidance to facilitate counselees' psychosocial adjustment. We explored networks of inter‐relationships among coping strategies and specific psychosocial difficulties in women tested for hereditary breast or ovarian cancer. Methods: Of 752 counselees consecutively approached, 646 (86%) completed questionnaires addressing coping strategies (Brief‐COPE) and psychosocial difficulties (PAHC) after the initial genetic consultation (T1), and 460 (61%) of them again after the test result (T2). We applied network analysis comparing partial correlations among these questionnaire scales, according to the type of genetic test ‐ single gene‐targeted or multigene panel, test result and, before and after testing. Results: Overall, 98 (21.3%), 259 (56.3%), 59 (12.8%) and 44 (9.6%) women received a pathogenic variant, uninformative negative (panel testing), variant of uncertain significance (VUS) or true negative (targeted testing) result, respectively. In most networks, connections were strongest between avoidance and general negative emotions. Cognitive restructuring was inter‐related to lower psychosocial difficulties. Avoidance and familial/social relationship difficulties were strongly related in women receiving a pathogenic variant. Stronger inter‐relationships were also noticed between avoidance and worries about personal cancer and concerns about hereditary predisposition in women receiving a VUS result. Differences in the prominence of inter‐relationships were observed by type of testing and assessment time. Conclusions: Network analysis may be fruitful to highlight prominent inter‐relationships among coping strategies and psychosocial difficulties, in women tested for HBOC susceptibility, offering guidance for counseling.